Apolipoprotein E gene polymorphism, serum lipids, and risk of superficial fungal infections in Egyptian patients - A preliminary case-controlled study - Amany I Mustafa; Ghada M Shams; Eman M Fawzy; Naglaa F Alhusseini; Rana A Khashaba; Ola S EL-Shimi (Wolters Kluwer Medknow Publications, 2023)
Background: Apolipoprotein E (APOE) gene isoforms have been found to affect the risk of superficial fungal infections (SFIs). However, the data only cover a few ethnicities. Aims: The present work intended to investigate the association of APOE gene polymorphism and serum lipids with the susceptibility of SFIs among a group of Egyptian patients. Materials and Methods: Standard laboratory methods were used to estimate the serum lipid profile, and polymerase chain reaction-restriction fragment length polymorphism was used to detect APOE gene polymorphism in deoxyribonucleic acid extracted from 150 SFI patients and an equal number of apparently healthy matched controls. Results: Serum total cholesterol, triglycerides, and low-density lipoprotein cholesterol were significantly higher in the studied patients than in controls. The APOE gene ε2, ε4 alleles, and ε3/4 and ε3/2 genotypes were significantly distributed in the patients than in the controls. APOE ε3/3 genotype was predominant in dermatophytosis and tinea versicolour patients, and ε3/4 genotype was predominant in candidiasis. Conclusions: ApoE alleles ε2 and ε4, and genotypes ε2/3 and ε3/4 are linked to SFI and may be risk factors, whereas allele ε3 and genotype ε3/3 may be protective for SFI in the Egyptian population studied. The lipid profile results suggest that hyperlipidemia may provide evidence for SFI pathogenesis. However; further large-scale studies are still needed to validate our results.